2017
DOI: 10.1136/annrheumdis-2016-210597
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs for spinal pain: a systematic review and meta-analysis

Abstract: NSAIDs are effective for spinal pain, but the magnitude of the difference in outcomes between the intervention and placebo groups is not clinically important. At present, there are no simple analgesics that provide clinically important effects for spinal pain over placebo. There is an urgent need to develop new drug therapies for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 62 publications
(32 reference statements)
3
105
0
10
Order By: Relevance
“…‐ 10 A recent Cochrane systematic review (1825 participants) found that paracetamol does not result in better outcomes compared with placebo for patients with acute LBP, and its effect on chronic LBP is uncertain 24 . Non‐steroidal anti‐inflammatory drugs are endorsed in three of the four guidelines (moderate quality evidence), 7 , 9 , 10 which is consistent with a recent systematic review demonstrating the efficacy of this class of medicine for both acute and chronic LBP 25 . However, the effect size for acute LBP is small (− 6.1 points [95% CI, − 9.5 to − 2.8] on a 0–100 scale) and some have argued that this may be too small to be clinically worthwhile 25 .…”
Section: Treating Non‐specific Low Back Painsupporting
confidence: 56%
“…‐ 10 A recent Cochrane systematic review (1825 participants) found that paracetamol does not result in better outcomes compared with placebo for patients with acute LBP, and its effect on chronic LBP is uncertain 24 . Non‐steroidal anti‐inflammatory drugs are endorsed in three of the four guidelines (moderate quality evidence), 7 , 9 , 10 which is consistent with a recent systematic review demonstrating the efficacy of this class of medicine for both acute and chronic LBP 25 . However, the effect size for acute LBP is small (− 6.1 points [95% CI, − 9.5 to − 2.8] on a 0–100 scale) and some have argued that this may be too small to be clinically worthwhile 25 .…”
Section: Treating Non‐specific Low Back Painsupporting
confidence: 56%
“…In a systematic review, Zulman et al found that pharmacologic interventions were assessed in 68.9% of the RCTs for older adults with complex health issues, whereas our results revealed that pharmacologic agents were planned for only 27.4% of the protocols. Perhaps this difference is due to the limited effectiveness of pharmacologic interventions for LBP in the literature . More important than not showing the efficacy of pharmacologic agents, the exclusion of older adults from these CTs prevent the development of knowledge regarding adverse events …”
Section: Discussionmentioning
confidence: 99%
“…Sciatica is usually treated with non-steroidal anti-inflammatory drugs, but there is a lack of consensus regarding the efficacy of these drugs [7]. As a result, some patients turn to acupuncture for which there is some evidence of efficacy in treating painful symptoms associated with sciatica [8].…”
Section: Discussionmentioning
confidence: 99%